Motivasi kerja karyawan bagian pabrik pt tirta mahakam resources tbk samarinda - Tengku Fahri Farisan; Yonathan Pongtuluran; Doddy Adhimursandi (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2017)
Conclusions of this study as follows: Needs physiological employees / factory workers already terpenui thus the motivation for physiological needs has been awarded by PT. Tirta Mahakam Resources Tbk. The security needs of employees / factory workers have been met with such motivation to security needs has been awarded by PT. Tirta Mahakam Resources Tbk. Social needs of employees / factory workers have been met with such motivation for social needs has been awarded by PT. Tirta Mahakam Resources Tbk. The need for employee appreciation / factory workers have been met with such motivation to security needs has been awarded by PT. Tirta Mahakam Resources Tbk. The need for self-actualization employees / factory workers have been met with such motivation for self-actualization has been awarded by PT. Tirta Mahakam Resources Tbk